2009
DOI: 10.1093/tropej/fmp025
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Status in Neonates Born to Pre-eclamptic Mother

Abstract: As pre-eclampsia is associated with increased oxidative stress and decreased anti-oxidant status, the results of these investigations suggest that oxidative stress and antioxidant status are altered towards proatherogenic level in cord blood of pre-eclamptic women which may ultimately be responsible for different complications of newborn babies of pre-eclamptic mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Oxidative stress has been suggested to influence histone acetylation and phosphorylation [143], telomere length [144] and vascular gene expression. Some oxidative stress is required for normal fetal development [145], but the ischaemic pre-eclamptic placenta has significantly decreased total antioxidant capacity compared with the normal placenta, and there is a correlation between levels of oxidative stress in maternal peripheral blood and cord blood in normotensive and pre-eclamptic pregnancies [146,147], with levels significantly higher in pre-eclampsia [127,147]. The levels of oxidative stress induced by pre-eclampsia itself are sufficient to cause damage to the fetus, as placental tissue samples have higher levels of oxidative DNA damage in pre-eclamptic pregnancies, whether or not there has been fetal growth restriction [148].…”
Section: Mechanism Of Long-term Programing? the Cardiovascular Systemmentioning
confidence: 99%
“…Oxidative stress has been suggested to influence histone acetylation and phosphorylation [143], telomere length [144] and vascular gene expression. Some oxidative stress is required for normal fetal development [145], but the ischaemic pre-eclamptic placenta has significantly decreased total antioxidant capacity compared with the normal placenta, and there is a correlation between levels of oxidative stress in maternal peripheral blood and cord blood in normotensive and pre-eclamptic pregnancies [146,147], with levels significantly higher in pre-eclampsia [127,147]. The levels of oxidative stress induced by pre-eclampsia itself are sufficient to cause damage to the fetus, as placental tissue samples have higher levels of oxidative DNA damage in pre-eclamptic pregnancies, whether or not there has been fetal growth restriction [148].…”
Section: Mechanism Of Long-term Programing? the Cardiovascular Systemmentioning
confidence: 99%
“…This is an indication of oxidative stress in preeclampsia/eclampsia. Signifi cant elevation of protein carbonyl level in maternal circulation [ 66 , 67 ] and cord blood [ 60 ] of preeclamptic mothers has been reported. The previous study showed higher plasma protein carbonyl levels that are markers of oxidative protein damage in preeclamptic pregnant women than those in healthy pregnant women [ 68 ].…”
Section: Oxidative Damage Markersmentioning
confidence: 99%
“…Cumulative evidence in recent years points towards biochemical imbalance in pre-eclampsia with an increase of oxidative stress and, at the same time, a deficient antioxidant protection. Significant elevation of malondiadehyde (MDA) levels in cord blood of pair matched pre-eclamptic mothers have been reported [21,22] whereas others have reported decline in its level [23] or no significant change [24,25] but Karabulut et al [26] inferred elevation of MDA levels in cord and mother during pre-eclamptic development compared to normal pregnancy. Similar contradictions exist about the level of antioxidant enzymes in the cord blood of pre-eclamptic mothers.…”
Section: Clinical Aspects Of Preeclampsiamentioning
confidence: 99%